The Role of the Indonesian Coffee Exporters Association (AEKI) In Encouraging Coffee Exports to the United States in 2016-2019 - Dimas Maya Silviani (Budapest International Research and Critics University, 2022)
This study aims to analyze the role of the Indonesian Coffee Expo Association to the United States in 2016-2019. Coffee products from Indonesia have been quite well known in foreign markets, especially the United States. Through the Indonesian Coffee Exporters and Industry Association (AEKI), farmers and entrepreneurs as well as Indonesian coffee industry players who are members of the membership want to assist the Indonesian government in exporting coffee to the United States as an effort to improve the National Economy. The Economy of the State will be strong if the individual economy is also strong, this is as stated by Andrew Moravcsik, the State exists as a forum for Individuals who become groups of Society.